Curcumin as an antidote to atrazine on estrogen homeostasis and beyond: mechanistic insights from a targeted literature review - Wright, Patrick J.; Ilali, Jade; Bu, Pengli (Frontiers in Endocrinology, 2025)
As the most common cancer in women globally, breast cancer poses a significant public health concern. More concerning is its rising incidence rates in certain areas of the world, including Australia, New Zealand, Western Europe, and North America. Exposure to environmental endocrine-disrupting chemicals may play a role. One such chemical is atrazine (ATZ), a man-made herbicide highly prevalent in the environment and detectable in drinking water, with reported levels ranging from 0.026 to 1.29 micrograms per liter (µg/L) in surface waters in the United States. During the development of breast cancer, many factors are involved, in particular the female sex hormone estrogen. Estrogen signaling fuels the proliferation and migration of estrogen receptor (ER)-positive breast cancer. The current review presents multiple lines of qualitative evidence from in vitro, in vivo, and epidemiological studies connecting ATZ exposure to processes important for breast cancer development. Specifically, ATZ’s stimulatory effect on breast cancer is mediated, at least partially, through enhanced CYP19A1 activity, the key enzyme converting testosterone to estradiol. ATZ stimulates CYP19A1 activity via parallel pathways, as evidenced by in vitro studies, potentially leading to elevated estradiol levels and estrogen signaling, which would then drive the development of ER-positive breast cancers. Beyond estrogen signaling, ATZ taps into the epidermal growth factor (EGF) signaling pathway to stimulate uncontrolled proliferation in human cell lines. We then show how curcumin, a phytochemical in turmeric, may counteract ATZ’s effect on the aforementioned processes. Once curcumin passes through the ADME process and becomes available in the human body, curcumin may possess effects to counter ATZ’s toxicity. Curcumin induces CYP3A4, as demonstrated by in vitro and in vivo studies, which catalyzes the degradation of steroid hormones, including estrogen. Curcumin downregulates the basal level of CYP19A1 in human cell lines via miRNA-125a and estrogen-related receptor alpha (ERRα), indicating an ability to dampen estrogen signaling. In addition, curcumin has been shown to inhibit the EGF receptor in human cell lines, thus blocking the EGF signaling cascade at the receptor level. Furthermore, curcumin may reduce ATZ’s overall bioavailability. ATZ and its metabolites undergo glutathione (GSH) conjugation followed by renal excretion. Curcumin helps maintain the GSH pool and activates glutathione-S-transferase (GST) in rats, thereby potentially facilitating the detoxification and elimination of ATZ. In conclusion, we propose that curcumin’s ability to induce CYP3A4, suppress CYP19A1, inhibit EGF signaling, and promote detoxification and elimination of ATZ makes curcumin a promising candidate for a mechanism-based antidote to ATZ toxicity.